2010
DOI: 10.1107/s0108270110005846
|View full text |Cite
|
Sign up to set email alerts
|

C—H...π interactions in cocrystals of bis(trimethylsilyl)acetylene and diphenylacetylene with benzene

Abstract: We present here the crystal structures of two acetylene derivatives cocrystallized with benzene, namely bis(trimethylsilyl)acetylene benzene solvate, C(8)H(18)Si(2).C(6)H(6), (I), and diphenylacetylene benzene solvate, C(14)H(10).C(6)H(6), (II). In (I), both molecules belong to the symmetry point group C(2h) and are located about special positions with site symmetry 2/m. In (II), both molecules show crystallographic inversion symmetry. In both structures, there are C-H...pi contacts between aromatic H atoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…The ethynyl groups of compound 3 are related by a C 3 axis and point away from each other. The C-Si bond lengths in compound 3 have a mean value of 1.859 Å, which compares well with the corresponding values (1.860 [29] and 1.832 Å [30] ) in compounds with Si-C≡C-Si segments previously reported in the literature. [29][30][31][32][33][34] The C≡C triple bonds exhibit a length of 1.208(3) Å [C(4)-C(5)], which correlates well with the values of related compounds.…”
Section: Synthesis Of Tris(dimethylsilyl)methane Scaffoldssupporting
confidence: 87%
See 3 more Smart Citations
“…The ethynyl groups of compound 3 are related by a C 3 axis and point away from each other. The C-Si bond lengths in compound 3 have a mean value of 1.859 Å, which compares well with the corresponding values (1.860 [29] and 1.832 Å [30] ) in compounds with Si-C≡C-Si segments previously reported in the literature. [29][30][31][32][33][34] The C≡C triple bonds exhibit a length of 1.208(3) Å [C(4)-C(5)], which correlates well with the values of related compounds.…”
Section: Synthesis Of Tris(dimethylsilyl)methane Scaffoldssupporting
confidence: 87%
“…The C-Si bond lengths in compound 3 have a mean value of 1.859 Å, which compares well with the corresponding values (1.860 [29] and 1.832 Å [30] ) in compounds with Si-C≡C-Si segments previously reported in the literature. [29][30][31][32][33][34] The C≡C triple bonds exhibit a length of 1.208(3) Å [C(4)-C(5)], which correlates well with the values of related compounds. [29][30][31][32][33][34] The angles of 3 have no irregularities except for the wide Si and other known molecules with a Si-C≡C-Si segment.…”
Section: Synthesis Of Tris(dimethylsilyl)methane Scaffoldssupporting
confidence: 87%
See 2 more Smart Citations
“…DFT analysis of the structure and bonding in the zirconium complexes showed that the electron density of the ring unit is reduced by the terminal [NSiMe 3 ] group, which results in a higher polarity of the M-N and N-S bonds. [20] As shown in Figure 3, no interaction of the alkyne with the fulvene is observed in this case. In many cases, fulvene formation has been observed in the presence of basic ligands; [19] however, to the best of our knowledge, this reaction is one of the few examples in which the formal elimination of a Cp* ligand such as 3 from the titanium centre at moderate temperature and without irradiation with light was proven by isolation of the corresponding C-H activated product.…”
Section: Resultsmentioning
confidence: 59%